The Heroon of Trokondas the Second at Kitanaura: Revised Dating - Prikhodko, Elena V. (Actual Problems of Theory and History of Art, 2024)
The city of Kitanaura was located on the border of Lycia and Pisidia on the flat top of a high isolated rock rising above a plateau in the mountains. The ruins of the city were initially discovered on April 6, 1842, by T. Spratt, followed by J. Schönborn, who made a similar discovery two days later. The most famous structure of the Kitanaura necropolis is the heroon, or monumental tomb of Trokondas II, erected on the hillside above the road leading into the city. The article provides a detailed description of the architectural features and decorative elements of the building, along with a translation of the funerary inscription carved on the architrave above the tomb’s entrance. Additionally, it presents the arguments of the archaeologists who surveyed Kitanaura, which suggest that the heroon was constructed in the 1st century AD. However, the analysis of inscriptions documenting specific events in the lives of Trokondas II’s descendants allows for a more precise dating of the heroon’s construction. It can be concluded that the heroon was built after the birth of Trokondas IV, grandson of Trokondas II, and the earliest possible date of his birth, if we count backwards from the birth of his great-grandson Marcus Aurelius Asclepiades, is 110 AD, or even later 125 AD. Consequently, it appears that the heroon of Trokondas II was erected in the 2nd to 4th decades of the 2nd century.
Keywords: Lycia; Pisidia; Kitanaura; Saraycık; heroon of Trokondas II; monumental tomb; tomb reliefs; Termessos; ancient Greek inscription